On fundamental group of Riemannian manifolds with ommited fractal subsets - Mirzaie, R. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We show that if K is a closed and bounded subset of a Riemannian manifold M of dimension m > 3, and the fractal dimension of K is less than m - 3, then the fundamental groups of M and M - K are isomorphic.